The freeze on mass media campaigns in England: a natural experiment of the impact of tobacco control campaigns on quitting behaviour - Langley, Tessa; Szatkowski, Lisa; Lewis, Sarah; McNeill, Ann; Gilmore, Anna; Salway, Ruth; Sims, Michelle (Wiley, 2014)
Aims